СЕЛЬСКОЕ ХОЗЯЙСТВО КАРАКАЛПАКСТАНА В 1985-1990 гг. ЧАСТЬ II. ПРОБЛЕМЫ ВНЕДРЕНИЯ НОВЫХ ЭКОНОМИЧЕСКИХ ОТНОШЕНИЙ - Сарыбаев, М.К. (SCIENCE and SOCIETY, 2025)
The article reveals the problems of formation of new economic relations on agroculture of Karakalpakstan in second half of 80 years of ХХ th century.
Keywords: diversity of economic forms of management; agricultural sector of the economy of Karakalpakstan; shortcomings and omissions; previous methods of management and management of the economy